2019
DOI: 10.1152/advan.00165.2018
|View full text |Cite
|
Sign up to set email alerts
|

Increased learning by using board game on muscular system physiology compared with guided study

Abstract: The aim of this work is to describe the “Muscular System Game,” created to assist in the teaching-learning process concerning the physiology of the muscular system, and to evaluate its effect on the learning of university students. Participating in this study were first-year undergraduate students of the pharmacy course (game group, n = 21, 5 men and 16 women, age 23.57 ± 4.92 yr) and the nursing course (control group, n = 22, 2 men and 20 women, age 22.90 ± 4.93 yr), who had the same level of preparation. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
5
15
0
Order By: Relevance
“…This was evidenced by the improvement in the test scores and by the decrease in the number of incorrect answers provided by the students who performed the portfolio activity. The portfolio method, as well as other active teaching strategies (11,12,31,32,(37)(38)(39), can increase the students' interest and knowledge retention, promote interaction among the students, and stimulate problem-solving.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was evidenced by the improvement in the test scores and by the decrease in the number of incorrect answers provided by the students who performed the portfolio activity. The portfolio method, as well as other active teaching strategies (11,12,31,32,(37)(38)(39), can increase the students' interest and knowledge retention, promote interaction among the students, and stimulate problem-solving.…”
Section: Discussionmentioning
confidence: 99%
“…The CMT and ICT tests performed by the students from years 2018 and 2019 had the same number of questions, the same question types (written answer, MCQ, and association questions), and the same complexity, and the students had the same time to answer the tests. A similar protocol was presented by Luchi et al (12). Therefore, the only difference between the classes (comparing years 2018 and 2019) was the portfolio group work activity.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The aims of this work were to describe the development process of the online digital version of the cardiac cycle puzzle, and to evaluate the student's perception of the utility of the digital game for their learning, during emergency remote teaching due to COVID-19 pandemic. challenge for them to be focused when old teaching methods are used (Abdulmajed et al 2015;Luchi et al 2019). In addition, although traditional lecture-based class is effective to present information, it did not promote deep and longlasting learning or development of problem-solving skills (Campos et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our objective was to develop a sound level of foundational disciplinary knowledge and promote "self-efficacy," which builds confidence in students, motivating them toward selfdirected learning (6). As many studies have reported the positive impact of digital educational games on student learning (6)(7)(8)(9)(10)(11)(12)(13), we chose to develop a card-matching game to teach physiological language and interrelationships. Our game, called eFlip, was conceived as a student-centered, mobile, online game that could be accessed easily at any time.…”
Section: Introductionmentioning
confidence: 99%